Awareness workshops on Alzheimer's disease in elderly people/family: contributions to health knowledge - Ilha, Silomar (2021)
This article aimed to describe the contributions of awareness workshops for the knowledge of academics from health care courses about Alzheimer's disease in the elderly/family. A semi-structured interview was carried out, before and after awareness-raising workshops with 12 academics from the health courses of a University of Rio Grande do Sul. There were findings about the academics' perception about Alzheimer's disease; risk factors, diagnosis and treatment for Alzheimer's disease and on the perception of the family in the context of the disease.